Between Money and Sovereignty: Is a New Monetary Thinking Needed to Institute the Common? - Lucarelli, Stefano (Praktyka Teoretyczna, 2018)
The diffusion of alternative financial and credit circuits, in which the money favours the self-management of social wealth, may curb the expropriation caused by processes of abnormal indebtedness that increasingly characterise economic systems. The article proposes an examination of four experiences with complementary currencies that have sprung up in Europe after the recent crisis, distinguishing between local currencies (Sardex, SoNantes and Sol Violette) and crypto coins (Bitcoin). The possibility of taking advantage of the monetary know-how that animates various experiences (like crypto coins and local clearing houses) would contribute to the re-thinking money as a social institution. Three main topics are discussed: 1. the “political technologies” in which the alternative monetary circuits consist; 2. democratic participation in the decision-making processes that characterise them; and 3. the meaning of the sovereignties that they potentially define